Corruption and development : a microeconomic analysis - (:unkn) unknown (My University, 2019)
This thesis proposes to study the effects of corruption on different development issues by focusing on three regions where the incidence of this phenomenon is particularly important: West Africa, Peru and Vietnam. This study differentiates the perception of corruption from its experience as well as the nature of corruption according to its purpose and reveals diverging effects. Having paid bribes promotes willingness to register among heads of informal West African production units and not to remain informal by avoiding official controls. In Vietnam, pro active (voluntary) payments provide small and medium manufactured firms an advantage over their competitors, but we can not say that corruption improves firms’ performance. Finally perception and experience of corruption have different effects on institutional trust among Peruvian households. The perception of corruption significantly reduces citizens’ confidence in the institutions of their country, which confirms the historical legacy of corruption scandals in the higher spheres of the State.
Keywords: African Research